A non-invasive method for quantitative monitoring of quality changes and water migration in bigeye tuna (Thunnus obesus) during simulated cold chain logistics using low-field nuclear magnetic resonance coupled with PCA - Wang, Xin-Yun (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2020)
Bigeye tuna (Thunnus obesus) is an important fish species worldwide due to its desirable flavour and rich nutrition. Cold chain logistics is one of the most common methods to store and sell bigeye tuna (Thunnus obesus). The purpose of this study was to investigate how bigeye tuna (T. obesus) deteriorate during simulated cold chain logistics with fluctuating temperatures by monitoring the quality changes and water distribution. The physical and chemical results showed that the sensory score, texture profile analysis (TPA), and water holding capacity (WHC) decreased, while total volatile basic nitrogen (TVB-N), K value, aerobic plate counts (APC), and psychrotrophic bacterial counts increased with fluctuating temperatures during 132 h. Low-field nuclear magnetic resonance (LF-NMR) and magnetic resonance imaging (MRI) detection showed that the T21 (trapped water) and proton density decreased, while T22 (free water) decreased initially and then increased, indicating continuous water loss and water migration during storage. Principal component analysis (PCA) revealed that springiness, hardness, chewiness, T21, and sensory score were correlated with each other (p < 0.05) and the linear combination of quality indicators and T2transverse relaxation time was established. Besides, temperature fluctuation (batch 3) accelerated the deterioration of bigeye tuna according to the comprehensive score of PCA. Results were based on LF-NMR which can be used to monitor quality changes in a fast non-invasive manner